Propaganda and Persuasion - Jowett, Garth R.; O'Donnell, Victoria (Newbury Park : Sage Pub., 1978)
Because children are exposed to highly professional sales pitches on television and because the old material produced by the Institute of Propaganda Analysis is outdated and in error, a new tool for the analysis of propaganda and persuasion is called for. Such a tool is the intensify/downplay pattern analysis chart, which includes the basic intensify/downplay pattern and paragraphs discussing propaganda, persuasion, and advertising. The chart has received considerable favorable comment from scholars and from respondents outside the academic community, including the National Council of Teachers of English Committee on Public Doublespeak. As a simplified tool for analyzing any human communication (verbal, nonverbal, and symbolic), it has the virtue of making clear not only what has been emphasized in a particular pitch but also what has been deemphasized. It can be used by children as well as by such groups as Nader's Raiders and Congressional committees. (A copy of the pattern accompanies the paper.) (TJ)
Includes bibliographical references and index.
Microfiche.
Keywords: Propaganda; Rhetorical Criticism; Speech Communication; Television; Television Commercials; Doublespeak; Speeches/Meeting Papers